Pemanfatan Arima Untuk Prediksi Harga Emas Dalam Sistem Rekomendasi Trading Gold Option - Yuliana Melita Pranoto; Reddy Alexandro Harianto; Iswanto Iswanto (STMIK Budi Darma, 2020)
In gold option trading, it is necessary to analyze both fundamental and technical data. In this study technical analysis is used to predict Gold Prices to help traders in making decisions. ARIMA is a method that completely ignores the independent variables in forecasting and is able to be a solution to predict gold prices and is used for the gold trading recommendation system. This is evidenced by the validation of high MAD = 16.93, MSE = 453.00, MAPE = 1.13%. And validation is low MAD = 12.23, MSE = 237.54, MAPE = 0.83%. And validation low MAD = 16.76, MSE = 576.32, MAPE = 1.12%. The results of the recommendation system from the ten trials predicted by Arima are recommended. When compared to the price in the field the target profit is 7% per week from ten experiments if on average the profit has exceeded the target.